Letters to Lipski, or, Bijay Krishna explained - Sāmanta, Rāimohana (H. Devi, 1977)
Author's correspondence with Alexander Lipski, b. 1919, on the philosophy and teachings of Vijaya Krishna Goswami, 1841-1899, Vaishnavite leader from Bengal.